2012
DOI: 10.1002/pro.2023
|View full text |Cite
|
Sign up to set email alerts
|

Morin hydrate inhibits amyloid formation by islet amyloid polypeptide and disaggregates amyloid fibers

Abstract: The polypeptide hormone Islet Amyloid Polypeptide (IAPP, amylin) is responsible for islet amyloid formation in type-2 diabetes and in islet cell transplants, where it may contribute to graft failure. Human IAPP is extremely amyloidogenic and fewer inhibitors of IAPP amyloid formation have been reported than for the Alzheimer's Ab peptide or for a-synuclein. The ability of a set of hydroxyflavones to inhibit IAPP amyloid formation was tested. Fluorescence detected thioflavin-Tbinding assays are the most popular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 51 publications
4
93
0
1
Order By: Relevance
“…Quercetin and myricetin efficacy as amyloid aggregation inhibitors and preformed fibril destabilizers was confirmed with insulin and α-syn, respectively [262,263]; yet, other compelling results were also reported: Jagota et al [264] suggested that quercetin inhibits Aβ fibrillization, but not its toxic oligomerization, hence increasing Aβ toxicity in a C. elegans model of Aβ deposition; Noor et al [265] reported that quercetin and myricetin were not able to prevent hIAPP fibrillation, at variance with morin (which differs only for the position and/or the number of the hydroxyl groups on the B ring). However, they did not investigate the possible effects of the two flavonols either on the most harmful oligomeric species or on aggregate toxicity.…”
Section: The Anti-amyloid Properties Of Natural Phenols and Polyphmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin and myricetin efficacy as amyloid aggregation inhibitors and preformed fibril destabilizers was confirmed with insulin and α-syn, respectively [262,263]; yet, other compelling results were also reported: Jagota et al [264] suggested that quercetin inhibits Aβ fibrillization, but not its toxic oligomerization, hence increasing Aβ toxicity in a C. elegans model of Aβ deposition; Noor et al [265] reported that quercetin and myricetin were not able to prevent hIAPP fibrillation, at variance with morin (which differs only for the position and/or the number of the hydroxyl groups on the B ring). However, they did not investigate the possible effects of the two flavonols either on the most harmful oligomeric species or on aggregate toxicity.…”
Section: The Anti-amyloid Properties Of Natural Phenols and Polyphmentioning
confidence: 99%
“…The array of natural phenols being tested as potential inhibitors of amyloid aggregation becomes wider and wider every day and now includes also tannic acid [207,313] and the product of tannin hydrolysis ellagic acid [314]; several flavones, like apigenin [315,316], baicalein [315,317,318], kaempferol [260,261,263,264,271,319], morin [265,320,321], fisetin [259,260,321], rutin (the glycoside of quercetin with the disaccharide rutinose) [322,323] and luteolin [260,324]; rottlerin, already known as a PKC-δ inhibitor [325,326]; the anthocyanidin malvidin, the main responsible for the red color of wine [327]; the stilbenes piceatannol [328] and the resveratrol-derived dimer ɛ-viniferin glucoside [329]; and, finally, ferulic acid (related to trans-cinnamic acid) [189,263,264,330332]. …”
Section: The Anti-amyloid Properties Of Natural Phenols and Polyphmentioning
confidence: 99%
“…The search for inhibitors of amyloid fiber formation is an active area of research and particular attention has been focused on flavanols (415). Among the most potent inhibitors found to date is the ester of epigallocatechin and gallic acid, (−)-Epigallocatechin 3-Gallate [EGCG; (2 R ,3 R )-5,7-dihydroxy-2-(3,4,5-trihydroxyphenyl)-3,4-dihydro-2 H -1-benzopyran-3-yl 3,4,5-trihydroxybenzoate].…”
mentioning
confidence: 99%
“…The search for inhibitors of amyloid aggregation and amyloid formation is an active area of research, 1017 but comparatively few anti-amylin amyloid compounds have been developed, and the vast majority of those are not drug-like. Recently, the intriguing possibility that clinically relevant doses of aspirin and the nonsteroid anti-inflammatory drug (NSAID) ketoprofen may inhibit amylin amyloid formation and might disaggregate preformed amylin amyloid fibrils has been raised.…”
mentioning
confidence: 99%